Communication Challenges in the Baatar Jujuran Tradition of Banjar Tribe Marriage with the Concept of Symbolic Interaction - Renny Ismaya; Sanusi; Gt. Irhamni; Maman Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Banjar tribe has a series of marriage traditions, starting from basusuluh, badatang, bapayuan, to baatar jujuran. During the baatar jujuran process, interpersonal communication takes place between the men and women, accompanied by several symbolic Banjar customary rituals. This research aims to explore the challenges and barriers to communication in the baatar jujuran tradition in Banjar tribe marriages in Banjarmasin City. This qualitative study is analyzed using symbolic interaction theory. Informants are selected from community groups, cultural experts, and religious leaders through purposive sampling. The baatar jujuran tradition is no longer highly regarded in its execution in Banjarmasin City and is not considered a marketable value due to the weakening of Banjar culture and customs in the city. No communication barriers were encountered in the baatar jujuran process, whether due to differences in language, ethnicity, individual characteristics, or the COVID-19 pandemic. In terms of interpersonal communication, the most crucial aspect is that both parties can understand the purpose of the conversation. The communication process in baatar jujuran during the pandemic with health protocols did not hinder the baatar jujuran process. Positive perceptions from all those present and equality in the baatar jujuran process support more effective communication during the pandemic